Evolution Of The Malaysian Halal Certification System: The Viable System Model As The Diagnostic Framework - Khairul Akmaliah Adham; Alina Abdul Rahim; Adlin Masood; Nur Sa’adah Muhamad; Mohd Fuaad Said (UKM Press, 2024)
Indexed by MyCite